Effect of mitochondrial cytochrome c release and its redox state on the mitochondrial-dependent apoptotic cascade reaction and tenderization of yak meat during postmortem aging. (September 2018) - Wang, Linlin; Ma, Guoyuan; Zhang, Yubin; Shi, Xixiong; Han, Ling; Yu, Qunli; Zhao, Suonan; Ma, Junyi
Abstract: We aim to investigate the effect of mitochondrial cytochrome c release and its redox state on the mitochondrial-dependent apoptotic pathway and yak meat tenderization during postmortem aging. Results indicated that the internal environment factors considerably decreased, whereas mitochondrial dysfunction increased in the early stage (0–72 h). Moreover, the release of mitochondrial cytochrome c into the cytosol, which was an apoptotic early event and the apoptosome elements in the cytoplasm changed remarkably with the increase of aging time. Meanwhile, N, N, N′, N′-tetramethylphenylene-1, 4-diamine (TMPD) inhibited the mitochondrial apoptotic process and postmortem meat tenderization by influencing the redox state of cytochrome c and apoptotic factors. These findings confirmed that the internal environment factors in the muscles provided essential conditions for mitochondrial cytochrome c, which activated the mitochondrial apoptotic pathway by forming apoptosome complexes. The reduction state of cytochrome c produced by TMPD plays a negative role in the activation of the mitochondrial apoptotic cascade reaction and meat tenderization during postmortem aging. We conclude that mitochondrial cytochrome c release and oxidized cytochrome c plays a significant role in yak meat tenderization by regulating the mitochondrial apoptotic pathway. Graphical abstract: Unlabelled Image Highlights: The internal environment factors in muscles provide essential conditions for mitochondrial cytochrome c release and apoptosis. Oxidized cytochrome c plays a significant role in activating the mitochondrial apoptotic cascade reaction and meat tenderization by forming apoptosome complex.